The 22q11.2 Microdeletion in Pediatric Patients with Cleft Lip, Palate, or Both and Congenital Heart Disease: A Systematic Review - Cárdenas-Nieto, Diana; Forero-Castro, Maribel; Esteban-Pérez, Clara; Martínez-Lozano, Julio; Briceño-Balcázar, Ignacio (Journal of Pediatric Genetics, 2020)
The 22q11.2 deletion syndrome (22q11.2DS) is present in approximately 5 to 8% of patients with cleft lip, palate, or both (CL/P) and 75 to 80% of patients with congenital heart disease (CHD). In a literature review, we consider this association of 22q11.2DS in pediatric patients with CL/P and CHD. Early diagnosis of 22q11.2DS in pediatric patients with CL/P and CHD helps to optimize a multidisciplinary treatment approach for 22q11DS. Early diagnosis, thereby, can improve quality of life for these patients and awareness of other potential clinical implications that may require attention throughout the patient's life.
Keywords: 22q11.2DS; cleft lip and/or palate; congenital heart disease; systematic review